2010
DOI: 10.1007/s10278-010-9330-5
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Delays in Report Availability Caused by Incorrect Exam Status with Web-Based Issue Tracking: A Quality Initiative

Abstract: Many radiology information systems (RIS) cannot accept a final report from a dictation reporting system before the exam has been completed in the RIS by a technologist. A radiologist can still render a report in a reporting system once images are available, but the RIS and ancillary systems may not get the results because of the study's uncompleted status. This delay in completing the study caused an alarming number of delayed reports and was undetected by conventional RIS reporting techniques. We developed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…The contents of the questions were based on literature regarding PACS competence and education [1][2][3][4][5][6][7][8][9][10][11][13][14][15][16][17]. Multiple (and including similar) items were used to measure the constructs of PACS competence and education, and the questionnaire was piloted prior to distribution to ensure reliability and validity [18].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The contents of the questions were based on literature regarding PACS competence and education [1][2][3][4][5][6][7][8][9][10][11][13][14][15][16][17]. Multiple (and including similar) items were used to measure the constructs of PACS competence and education, and the questionnaire was piloted prior to distribution to ensure reliability and validity [18].…”
Section: Methodsmentioning
confidence: 99%
“…However, this depends on a number of factors and one of the major factors is the PACS competence of radiologic technologists (RTs) [1,4,[6][7][8][9][10]. If the RTs do not have adequate PACS competence, situations such as taking longer to complete radiologic examinations [4,6], mislabeling of images [9], wasting time to fix the mislabeling [7], and delay in reporting will happen [10]. Recently, the registering bodies such as American Society of Radiologic Technologists (ASRT) and Medical Radiation Practice Board of Australia have suggested that RTs need to have adequate PACS competence for their job and the PACS competence has been considered as one of the key competences of RTs [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This borrows from established principles in business intelligence and analytics, in which data analysis tools provide the means to make smaller evidence-based adjustments more frequently, providing increased transparency, fewer and smaller systemwide interruptions, and, theoretically, increased efficiency and quality [48]. The available applications are vast, including technologist feedback [46,47], radiologist workflow management [50][51][52], and overall departmental quality metrics [48,49,53]. The reader is referred to the reference material for specific details.…”
Section: Digital Dashboardsmentioning
confidence: 99%
“…Morgan et al [49] nicely summarize several factors that can increase the success of a dashboard: interface optimization, where there is concise presentation of only the relevant data at the appropriate time; context sensitivity, which should account for the variability in needs between different users; user customization, to improve user satisfaction and account for interindividual preferences; and workflow integration, because nonintegrated systems have been shown to have a poor impact on end behaviors [52,54]. Perhaps most important, there must be a system in place to drive change on the basis of the information acquired, whether through real-time alert systems [50], individual self-assessment [51], or organized departmental meetings [48].…”
Section: Digital Dashboardsmentioning
confidence: 99%